Perlindungan Hukum Kepada Anak Yang Melakukan Tindak Pidana - Sri Purwanti Budi Utami; Anggraeni Endah Kusumaningrum (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
This study is entitled "Legal Protection of Children as Criminal Actors. Nowadays there are often criminal acts committed by children. The problem in this study is the legal protection for children as perpetrators of crime in accordance with the juvenile criminal justice system in Indonesia and its implementation in the Merauke region. The research method used is a juridical-empirical legal research method with a fact and legislation approach. The existing law is used as a guideline about what people should and should not do and see the phenomena that occur in the field. The forms of protection provided to children in conflict with the law are based on Law no. 11 of 2012 concerning the Child Criminal Justice System, which provides protection to children in the stages of arrest and detention, investigation, prosecution, trial and coaching, and through the application of diversion. The conclusion of this study is that children as perpetrators of torture must be treated humanely, accompanied, provided with special facilities and infrastructure as well as sanctions given to children in accordance with the principle of the child's best interests.